Abstract Book of the 9th International Congress on Science and Skiing (ICSS), March 18 - 22, 2023, Saalbach-Hinterglemm, Austria (9th International Congress on Science and Skiing, March 18 - 22, 2023, Saalbach-Hinterglemm, Austria, 2023)
The Department of Sport and Exercise Science at the University of Salzburg is proud to present the Abstract Book of the 9th International Congress on Science and Skiing (ICSS 2023), held in Saalbach-Hinterglemm, Austria, from March 18 - 22, 2023. The scientific programme offers a broad interdisciplinary spectrum of research in Nordic and alpine skiing and snowboarding. The highlights of the congress will be the four keynotes presented by Hans-Christer Holmberg (SWE), John Seifert (USA), Vesa Linnamo (FIN), and Nils Haller (GER).